Image capturing fake user of mobile phone using front camera / Dr Mohd Afizi Mohd Shukran - Mohd Shukran, Dr Mohd Afizi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Image Capturing Fake User of Mobile Phone Using Front Camera ia a system design to protect the security of information and also Android mobile users. This system serves a s a lock screen where the user is required to enter the password set in the system. Like other lock screen key, the system has the same functions but in the event of fault password for three times, the system will take the user's photo. After the process of taking pictures automatically without user knowledge occurs, the system will continue to send pictures to the user Dropbox's account. Concepts used by this project is adapting existing technology of mobile phone front camera as the most important element to take pictures of the user. As a result, the system can capture consumers who are trying to break into legitimate users' mobile phones.